2017
DOI: 10.1111/1755-0998.12654
|View full text |Cite
|
Sign up to set email alerts
|

Minimum sample sizes for population genomics: an empirical study from an Amazonian plant species

Abstract: High-throughput DNA sequencing facilitates the analysis of large portions of the genome in nonmodel organisms, ensuring high accuracy of population genetic parameters. However, empirical studies evaluating the appropriate sample size for these kinds of studies are still scarce. In this study, we use double-digest restriction-associated DNA sequencing (ddRADseq) to recover thousands of single nucleotide polymorphisms (SNPs) for two physically isolated populations of Amphirrhox longifolia (Violaceae), a nonmodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
260
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(274 citation statements)
references
References 58 publications
10
260
3
1
Order By: Relevance
“…This was observed whatever the species and the panel of variants, and the effect was especially strong when measuring population differentiation and linkage disequilibrium, even greater than the effect of variant density. Our findings disagree with Nazareno, Bemmels, Dick, and Lohmann () who showed that accurate estimates of F ST between two Violaceae populations could be obtained with down to two individuals and about 1,500 SNPs. In our case the sample size effects reported could also be associated to the finescale structure of wild samples (i.e., substructures in Asiatic mouflon and Bezoar ibex groups that do not correspond to true populations) illustrated by high inbreeding between some individuals (Table ) and sNMF results (Figure S16).…”
Section: Discussioncontrasting
confidence: 99%
“…This was observed whatever the species and the panel of variants, and the effect was especially strong when measuring population differentiation and linkage disequilibrium, even greater than the effect of variant density. Our findings disagree with Nazareno, Bemmels, Dick, and Lohmann () who showed that accurate estimates of F ST between two Violaceae populations could be obtained with down to two individuals and about 1,500 SNPs. In our case the sample size effects reported could also be associated to the finescale structure of wild samples (i.e., substructures in Asiatic mouflon and Bezoar ibex groups that do not correspond to true populations) illustrated by high inbreeding between some individuals (Table ) and sNMF results (Figure S16).…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, leaves from six individuals were obtained per sampling location. The typical limitations of small sample sizes are offset by large numbers of SNPs (Nazareno, Dick, et al., ; Willing, Dreyer, & van Oosterhout, ; Senn et al., ), which permit high‐resolution identification of genetic structure (Brown et al, ; Puckett et al, ; Trucchi et al, ; Kotsakiozi et al, ; Nazareno, Bemmels, Dick, & Lohmann, ). For example, in a previous study of Amphirrhox longifolia , Nazareno, Dick, et al.…”
Section: Methodsmentioning
confidence: 99%
“…Four genomic libraries were created using a double digest RADseq protocol (Peterson et al., ), with the modifications proposed by Nazareno, Bemmels, et al. () to minimize variance in the number of reads per individual within each pool. Double‐stranded DNA concentrations were quantified before digestion reactions using the Qubit dsDNA Assay Kit (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic material is both easy and inexpensive to sample (Schwartz, Luikart, & Waples, ), and recent advances in sequencing technology and bioinformatics allow researchers to harvest information from across the genome at low cost. Furthermore, reliable estimates of both genetic diversity and past population size have been recovered from sample sizes as small as a single individual (Li & Durbin, ; Nazareno, Bemmels, Dick, & Lohmann, ). However, historical signals of demographic processes can weaken the relationship between census and effective population size, and thus the relationship between abundance and heterozygosity (Frankham, ).…”
Section: Introductionmentioning
confidence: 99%